The level of physical training modulates cytokine levels through P2X7 receptor in healthy subjects. (16th January 2018) - Comassi, Mario; Santini, Eleonora; Rossi, Chiara; Vitolo, Edoardo; Seghieri, Marta; Tocchini, Leonardo; Franzoni, Ferdinando; Solini, Anna
Abstract: Introduction: The P2X7 receptor‐NLRP3 inflammasome complex (P2X7R‐Infl) regulates inflammatory and immune responses. Physical exercise modulates heat‐shock proteins (Hsps), influencing cytokine levels and oxidative stress; Hsp72 triggers P2X7R‐Infl‐dependent responses. Subjects and Methods: We studied the effect of a single bout of maximal exercise on lymphomonocyte expression of P2X7R, NLRP3, caspase‐1, NF‐kB and Hsp72 and circulating levels of IL‐1β, IL‐18 and MCP‐1, all modulated by P2X7R‐Infl, in healthy sedentary (SED), trained (ATH), endurance (END) male individuals. Results: Baseline P2X7R, NLRP3 and Caspase‐1 expression progressively increased from SED to ATH and END; NF‐kβ showed the same trend. Hsp72 did not differ among groups. Acute exercise strongly reduced P2X7R in all participants, irrespective of their degree of physical training. Inflammasome responses differed across groups: in SED, NLRP3 and Caspase‐1 increased; in ATH, NLRP3 reduced and caspase‐1 did not vary; in END, NLRP3 and Caspase‐1 declined. Baseline IL‐1β, higher in END, was unmodified after exercise; IL‐18 decreased; MCP‐1 doubled in SED, did not vary in ATH, declined in END. In the whole study population, significant direct relationships emerged between P2X7R expression and IL‐1β, IL‐18, MCP‐1 levels, all P  < .001; also Caspase‐1 related with these markers. A multivariate analysis showed age, BMI and P2X7R as determinants of postexercise IL‐1β levels. Conclusion: Endurance show higher P2X7R‐Infl expression and function vs SED and ATH; however, maximal exercise determines prevailing pro‐inflammatory vs anti‐inflammatory responses in untrained and trained participants, respectively, highlighting a likely cause‐effect relationship between degree of physical activity and P2X7R‐Infl‐mediated responses.